Study on the X-ray mirror quality specification in advanced light source - Hu, Weishan; Cui, Xiaowen; Li, Ming; Sheng, Weifan; Zhang, Weiwei; Jia, Quanjie; Yang, Fugui (Frontiers in Physics, 2022)
The influence of the X-ray optics error on the performance of the beamline increases as the X-ray beam's coherence improves in advanced light source. The spatial dispersion of the X-ray beam is crucial for spatial resolution and field of view. However, selecting the appropriate merit function for expressing light dispersion and identifying its relationship to optical error is very important in beamline design. To address this issue, we develop a high-efficiency wave-optics simulation platform and deterministic analysis model. Merit functions including Strehl ratio, root-mean-square spot size, and encircled energy radius are evaluated by the simulation experiments. It proves that the encircled energy radius is a good metric of the x-ray beam spatial dispersion, which matches the results by the Church-Takacs theory. In addition, it is found that limiting the contribution of the low frequency (wavelength > L/10) error is effective for specifying requirement of X-ray mirror quality.